A Morphological Analysis of Reduplication in the Javanese Short Movie Anak Lanang - Khanandya Nila Ulfa; Deliana Deliana (Hasanuddin University, 2025)
This study investigates the morphological process of reduplication in the Javanese language as used in the short movie Anak Lanang. Using Rubino’s (2005) structural typology as the analytical framework, the research identifies and classifies eleven reduplicated forms found in the film’s dialogue. The data were analyzed descriptively by first extracting reduplicated items from the transcription, then categorizing them into the types that emerged: full reduplication, partial reduplication, sound-modifying reduplication, and affixed reduplication. Each item was examined for its morphological structure, part of speech, and semantic function, supported by English translations for clarity. The findings show that full reduplication is the most frequently used type, serving functions such as plurality, intensity, habitual action, and gradual processes. Partial reduplication and sound-modifying reduplication contribute to derivational and expressive meanings, while affixed reduplication—common in Austronesian languages—forms activity and behavioral nouns through the addition of the suffix –an. Overall, the study demonstrates that reduplication remains a productive and multifunctional feature of Javanese morphology, actively shaping meaning in natural conversational contexts. These results reinforce the importance of reduplication in the linguistic system of Javanese and highlight its role in everyday communication.